Turnover Intention among Staff Who Support Older Adults Living Alone in Japan: A Cross-Sectional Study - Hisao Nakai; Kuniko Ishii; Takako Sagino (Social Sciences, 2024)
Older adults in Japan traditionally rely on family members for care. However, the growing number of older people living alone has increased staff burden in community general support centers (CGSCs), which provide care for older people in Japan. This study aimed to identify factors linked to turnover intention among CGSC staff. Of 1002 staff invited to participate, 283 completed a survey (response rate: 28.2%). Logistic regression analysis of 183 valid questionnaires examined demographic, job-related, and attitudinal factors associated with turnover intention. The results showed that the perceived difficulty of supporting older adults living alone was the main predictor of turnover intention. Staff reporting high perceived difficulty levels were more likely to consider leaving. Negative attitudes toward supporting this population also increased turnover risk. These findings highlight a pressing need for targeted interventions to strengthen the ability of CGSC staff to manage the challenges of caring for isolated older individuals. Addressing staff perceptions and providing essential training and resources could reduce turnover rates and increase the quality of care for this vulnerable group.